Characterization, Potential Prognostic Value, and Immune Heterogeneity of Cathepsin C in Diffuse Glioma - Zhou, Quanwei; Li, Shasha; Yan, Xuejun; Zhu, Hecheng; Liu, Weidong; Guo, Youwei; Xu, Hongjuan; Yin, Wen; Li, Xuewen; Yang, Qian; Liu, Hui; Jiang, Xingjun; et al. (Current Bioinformatics, 2023)
Background: Diffuse glioma is the most frequent intracranial tumor and remains universally lethal. Prognostic biomarkers have remained a focus in diffuse glioma during the last decades. More reliable predictors to adequately characterize the prognosis of diffuse glioma are essential. Cathepsin C (CTSC), a lysosomal cysteine protease, is an essential component of the lysosomal hydrolase family, with their potential roles in diffuse glioma remaining to be characterized. Objective: We aimed to investigate the performance of CTSC in predicting prognosis and therapeutic targets in diffuse glioma. Methods: The expression profile of CTSC in multiple tumors and more than 2000 glioma samples with corresponding clinical data were collected through authoritative public databases. The expression level of CTSC was evaluated by qPCR and IHC. The prognostic value of CTSC was assessed using the univariate and multivariate cox regression analysis. The ESTIMATE R package was used to evaluate the immune and stromal scores based on the gene expression profile. The CIBERSORT was applied to evaluate the relative levels of 22 immune cell subtypes by using the R package 'CIBERSORT' to define the cell composition of tumor tissues. In addition, the MCP counter was used to assess the absolute abundance of neutrophils. Results/Discussion: CTSC was aberrantly expressed and significantly correlated with clinical outcomes in multiple tumors. CTSC was heterogeneously expressed across histologic types and tumor grades for diffuse glioma and highly enriched in IDH or IDH1-wildtype glioma. CTSC was positively associated with immune and stromal scores and infiltrating levels of M2 macrophages and neutrophils and negatively associated with infiltrating levels of NK cells. Additionally, CTSC was closely correlated with some immune checkpoint molecules, including CD276, CD80, CD86 and PD-L2. Conclusion: CTSC was involved in shaping the immunosuppressive microenvironment and acted as an independent indicator of a poor prognosis in diffuse glioma. Targeting CTSC for glioma therapies might provide promising prospects.
Keywords: immune checkpoint molecules